Synthesis and biological activity study of some novel Tri-Schiff's basses derived from 6-aminopenicillanic acid and Tri-amide containing three 1,3,4-thiadiazole units. - Radwan M. Ali Hameed (College of Pharmacy / Mustansiriyah University, 2009)
Reaction of meistylene with bromine under UV-light afforded α,α,α',α',α",α"-hexabromo mesitylene [2]. The reaction of compound [2] with morpholine and hydrochloric acid afforded 1,3,5-triformyl benzene [3]. Condensation of compound [3] with three equivalents of 6-aminopenicillanic acid afforded 1,3,5 tri[penicillanic acid]-6-N-trimesilydene [4]. The reaction of thiosemicarbazide and 4-n-alkoxy benzoic acid [6]n in POCl3 afforded the corresponding 2-amino-5-(4-n-alkoxyphenyl)-1,3,4- thiadiazole [7]n. condensation of 1,3,5-benzene tricarboxylic acid [5] with three equivalents of appropriate amino-thiadiazole [7]n afforded the corresponding Tri-amide compounds [8]n. The characterization of the synthesized compounds was elucidated by their melting points and different spectroscopic methods (UV, FT-IR) spectroscopy. The results are in agreement with the suggested structures. The synthesized compounds were tested in vitro for antimicrobial activity. The results obtained indicated that some of these compounds are more active than with others, Table (7).